Dionísio Del Santo: constructive outside of time - Hipólito, Rodrigo (Revista do Colóquio, 2025)
This article analyzes the exhibition “Dionísio Del Santo: Constructive Yesterday and Today” (2025). Curated by Felipe Scovino, it examines the reverberations of Brazilian constructivist thought across three generations of artists, establishing connections between Del Santo's work and contemporary pieces. This study considers works that share investigations into geometry, color, rhythm, and structure, highlighting the unique contribution of Del Santo to Brazilian constructivism through his anti-dogmatic stance. It also analyzes the dialogue between different artistic languages ​​– painting, screen printing, woodcut, sculpture, and installation – in order to demonstrate the persistence and transformation of constructivist principles in contemporary art. This research highlights how Del Santo moved between concrete art movements without programmatic affiliation, selectively appropriating procedures and maintaining creative autonomy. It concludes that the Brazilian constructivist tradition, as well as Del Santo's work, remains fertile ground for contemporary investigations and resists the historical periodization that would confine it to the 1960s-1980s.
Keywords: Dionísio Del Santo; brazilian constructivism; concretism; screen printing; art from Espírito Santo